Analisis Teori Habitus dalam Novel Normal People Karya Sally Rooney Berdasarkan Filsafat Sosial Pierre Bourdieu - Hukma Shabiyya (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: Normal People (2018) by Sally Rooney depicts miscommunication between the two main characters, Connell and Marianne. Externally, their miscommunication caused by different social classes. This issue can be analyzed through Pierre Bourdieu’s perspective. This research aims to discuss the analysis of habitus theory in Normal People by Sally Rooney. The data retrieval steps that is applied is qualitative approach by employing library research technique. Thus, the material object that is discussed is Normal People novel and viewed in the perspective of the formal object of Pierre Bourdieu’s habitus theory. The result indicates that habitus differentiation poses a barrier for Connell and Marianne in understanding one another, that barrier ultimately leads them to misunderstanding. The conclusion obtained is that it is found that social stratification in society not merely impacted equitable economic welfare, but also impacted how individuals communicate. This conclusion evidenced by the relationship dynamics between Connell and Marianne which can be analyzed through habitus theory. This research findings implicate to the development of study on Pierre Bourdieu’s habitus theory on Normal People by Sally Rooney.Key Words: Bourdieu, habitus, individual, Normal People, Rooney. Abstrak: Novel Normal People (2018) karya Sally Rooney menggambarkan miskomunikasi di antara dua tokoh utamanya, yakni Connell dan Marianne. Secara eksternal, miskomunikasi itu disebabkan oleh perbedaan kelas sosial. Hal itu dapat dianalisis melalui sudut pandang Pierre Bourdieu. Penelitian ini bertujuan untuk membahas analisis teori habitus Pierre Bourdieu dalam novel Normal People karya Sally Rooney. Langkah-langkah pencarian data yang diterapkan adalah pendekatan kualitatif dengan teknik studi kepustakaan. Dengan demikian, objek material yang dibahas adalah novel Normal People dan dilihat dalam perspektif objek formal teori habitus Pierre Bourdieu. Hasil pembahasan mengindikasikan bahwa diferensiasi habitus merupakan hambatan bagi Connell dan Marianne dalam memahami satu sama lain, hambatan tersebut pada akhirnya membawa mereka pada kesalahpahaman. Kesimpulan yang didapat ialah ternyata stratifikasi sosial di masyarakat tidak hanya berdampak pada pemerataan kesejahteraan ekonomi saja, tetapi juga berdampak pada cara individu berkomunikasi. Kesimpulan itu dibuktikan dengan dinamika hubungan Connell dan Marianne yang dapat dianalisis melalui teori habitus. Temuan penelitian ini berimplikasi pada pengembangan kajian tentang teori habitus Pierre Bourdieu dalam novel Normal People karya Sally Rooney.Kata Kunci: Bourdieu, habitus, individu, Normal People, Rooney.